The Influence of the Project Based Learning Model Integrated Independent Curriculum to Results Learn for Students of Class X Biotechnology Material SMK Islam Al-Azhar Jember - Khoirul Anam; Dwi Sucianingtyas Sukamto; Hanif Rafika Putri (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effect of the Project Based Learning model integrated with the Merdeka Curriculum on the learning outcomes of Grade X students in Biotechnology material at SMK Islam Al-Azhar Jember. The study employed a quasi-experimental approach with a pretest-posttest non-equivalent control group design. The sample consisted of 34 students who were given pretests and posttests to measure their biotechnology learning outcomes, using a learning outcome test as the instrument. The results showed a significant improvement in students’ learning outcomes after the implementation of the Project Based Learning model integrated with the Merdeka Curriculum, with the experimental group achieving a posttest average score of 89.73, compared to 76.21 in the control group. The N-Gain score for the experimental group reached 0.73 (73%), which is categorized as high, while the control group scored 0.56 (56%). A t-test indicated a significant difference between the two groups (p = 0.000 < 0.05). These findings indicate that the Project Based Learning model integrated with the Merdeka Curriculum is proven to be effective in improving Biotechnology learning outcomes.